An Evaluation of Indonesian Textbooks Using Revised Bloom’s Taxonomy - Denda Rinjaya; Sisilia Setiawati Halimi (IAIN MADURA, 2022)
Implementing higher-order thinking skills into teaching-learning practice has become a priority for any teaching program anywhere today. This study aims to evaluate two books of BIPA (Bahasa Indonesia bagi Penutur Asing) 7 Sahabatku Indonesia (2019) based on the Revised Bloom’s Taxonomy (RBT). The content analysis approach was used in this study to analyze research data in the form of instructions and questions classified using the RBT category. First, the analysis results showed that the instructions and questions in the two BIPA books were dominated by lower-order thinking skills (‘understanding' and 'remembering'). Second, although lower-order thinking skills dominated the instructions and questions in the two BIPA books, this study revealed that the majority of the instructions and questions classified as lower-order thinking skills in both textbooks analyzed can be changed into higher-order thinking skills. The findings of this study infer that the majority of instructions and questions in the BIPA 7 Sahabatku Indonesia need to be revised to encourage higher-order thinking skills-oriented teaching. These findings serve as a reminder for textbook writers of the importance of providing cognitive activities that can help learners develop both lower-order and higher-order thinking skills in textbooks.